Marginal cost of public funds and regulatory regimes: computable general equilibrium evaluation for Argentina - Chisari, Omar Osvaldo (2010)
We estimate the Marginal Cost of Public Funds for Argentina using a Computable General Equilibrium (CGE) model, assessing the sensitivity of the results to the existence of alternative regulatory regimes (price-cap and cost-plus) for public utilities subject to regulation. The estimates are in the range of international studies, and we confirm that the results are sensitive to the regulatory regime, to the presence of exempted goods, the existence of unemployment, the elasticity of labor supply, as well as to the degree of capital mobility, between sectors and internationally. In addition, our results highlight the existence of differential propensity to finance public projects under price-cap regimes vis-à -vis cost-plus regimes.